Review of Checkpoint Inhibitor Immunotherapy in Neuroendocrine Tumor of Prostate and Our Experience in 2 Cases - Akriti Pokhrel MD; Kiron Nair MD; Vijay Jaswani MD; Muhammad Salyana MD; Unni Mooppan MD; Jen C. Wang MD (SAGE Publishing, 2022)
Neuroendocrine prostate cancer (NEPC) is a rare entity. De novo NEPC is extremely rare; other cases are usually adenocarcinoma previously treated with hormonal therapies transforming to NEPC. Most of the cases are metastatic at diagnosis and regardless of the histology types, the prognosis is poor. In this report, we reviewed the checkpoint inhibitor (CPI) immunotherapies used for neuroendocrine tumors of the prostate. Very limited data with only a few cases were published which showed a limited activity by immunotherapy; therefore, we present our experience of 2 cases: (1) adenocarcinoma with foci of NEPC and (2) adenocarcinoma transforming to NEPC after treatment with androgen deprivation therapy (ADT); both of which were initially managed with ADT, chemotherapy followed by immunotherapy with durvalumab, a programmed death ligand 1 inhibitor. In these 2 cases, CPI therapy showed limited efficacy, suggesting that neuroendocrine histology is not very responsive to CPI treatment, regardless if onset is early or late. Other therapies need to be explored for the treatment of NEPC.